Arctic Migratory Raptor Selects Nesting Area During the Previous Breeding Season - Curk, Teja; Kulikova, Olga; Fufachev, Ivan; Wikelski, Martin; Safi, Kamran; Pokrovsky, Ivan (Frontiers in Ecology and Evolution, 2022)
Migratory species have a limited time for habitat selection upon arrival at the breeding grounds. This is especially evident in arctic migrants, which are restricted by a narrow window of opportunity when environmental conditions are favourable for breeding. This general time constraint is amplified in rough-legged buzzards (Buteo lagopus) who, as many other arctic predators, rely on rodent (lemming) cycles during the breeding season, a 3-5 year period of waxing and waning local food abundance. It remains unclear how arctic predators, especially migrants, can find nesting areas where rodents are numerous when their selection time is so limited. We hypothesized that rough-legged buzzards select nesting areas during the previous breeding season. We tracked 43 rough-legged buzzards using GPS telemetry and assessed their movements post-breeding prospecting behaviour to test our hypothesis. Here we show that rough-legged buzzards search for a nesting location during the previous breeding season in a post-breeding period. In the following year, individuals return to and attempt to breed in the area they inspected the year before. Rough-legged buzzards, regardless of breeding success, remained in the Arctic all breeding season until the end of September. Failed breeders prospected more than successful ones. At the same time, buzzards that bred in the rodent-free ecosystem prospected less and showed a high level of philopatry. Therefore, as rodent cycles have been predicted to collapse in the warming Arctic, we can expect arctic predators to change their movement patterns in the future with serious potential consequences for their conservation. We anticipate our study provides a step forward towards understanding movement and settlement decisions in animals experiencing high inter-annual environmental variation.